Synthesis of some new pyrazole and pyrimidine derivatives carrying a sulfonamide moiety of expected antitumor activity and study of the synergistic effect of γirradiation - Ghorab, Mostafa M; Ragab, Fatma A; Heiba, Helmy I; Youssef, Hanan A; Gala, Marwa (Arzneimittelforschung, 2010)
Several novel pyrazole (11–18) and pyri-midine (19–23) derivatives were synthesized starting from different sulfonamides and different active methylenes The synthesized compounds were characterized by elemental analysis, IR, 1H-NMR and mass spectral data. The obtained compounds were screened as antitumor agents against human tumor cell line. Some of the tested compounds were equipotent while the others were more potent than doxorubicin (CAS 25316-40-9). The synergistic effect with g-radiation was also studied.
Keywords: γ-Irradiation; Pyrazole derivative; Pyrimidine derivative; Sulfonamides, antitumor activity